Image Watermarking for Tamper Correction Based on Hamming Error Correcting Code - Rao, Pinapati Lakshmana; Sonar, Reshma; Boddu, Nanditha; Pradhan, Anita; Senapati, Ranjan K.; Swain, Gandharba (Engineering, Technology & Applied Science Research, 2025)
Watermarking techniques are designed to embed a watermark in a manner that enables precise detection of tampering at the receiver side. This article presents an image watermarking and tamper detection technique based on a modified Hamming code. The watermarking process is applied to each individual pixel of the gray image, with each pixel is represented using 8 bits. The 4 higher plane bits of a pixel are designated as data bits, and based on these, 3 redundant bits are computed. These 3 redundant bits are then modified using a Logistic Map (LM). Furthermore, based on the 4 data bits and 3 modified redundant bits, a parity bit is computed. The 3 modified redundant bits along with the parity bit form the Watermark Bits (WBs), which are embedded into the Least Significant Bit (LSB) positions of the pixel. This process results in a watermarked pixel. In the event that a single bit is tampered with, it can be easily identified and corrected at the receiver according to the detection and correction logic. The Hiding Capacity (HC) is 4 bits per pixel, and the distortion measure is 31 dB. Although the similarity index is reduced the accuracy of tamper detection is significantly improved.